Embolization for post‐partum rupture of ovarian artery aneurysm: Case report and review. Issue 4 (5th November 2014) - Sakaguchi, Isao; Ohba, Takashi; Ikeda, Osamu; Yamashita, Yasuyuki; Katabuchi, Hidetaka
Abstract Spontaneous rupture of an ovarian artery aneurysm most commonly presents with abdominal pain in a multiparous woman in the early post‐partum period. Aneurysms of the ovarian artery have been reported in the published work very infrequently. In our case, a 31‐year‐old multiparous woman experienced sudden left lower quadrant abdominal pain on the second post‐partum day. Angiography showed rupture of a left ovarian artery aneurysm, which was successfully embolized using gelatin sponge particles. The patient resumed menstruation 3 months after the embolization and concurrently conceived, ultimately giving birth at term without complications. Interventional radiology appears to be a highly safe and effective technique for diagnosis and management of a ruptured ovarian artery aneurysm with minimal risk of impairing subsequent fertility.